2018
DOI: 10.1093/annonc/mdy430.002
|View full text |Cite
|
Sign up to set email alerts
|

Phase I extension study of ETC-159 an oral PORCN inhibitor administered with bone protective treatment, in patients with advanced solid tumours

Abstract: Background: TRK fusion cancer results from gene fusions involving NTRK1, NTRK2 or NTRK3. Larotrectinib, the first selective TRK inhibitor, has demonstrated an overall response rate (ORR) of 75% with a favorable safety profile in the first 55 consecutively enrolled adult and pediatric patients with TRK fusion cancer (Drilon et al., NEJM 2018). Here, we report the clinical activity of larotrectinib in an additional 35 TRK fusion patients and provide updated follow-up of the primary analysis set (PAS) of 55 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It shows manageable side effects in interim analysis of a phase I trial in which this agent was evaluated in combination with denosumab in 5 patients. Dysgeusia (62%), fatigue (37%), weight loss (37%), back pain (37%) and headache (37%) were the most frequent AEs [128]. An ongoing trial is evaluating ETC-159 in endometrial cancer alone or in combination with pembrolizumab (NCT02521844).…”
Section: Agents Targeting Cscs In Ec: Clinical Trials and New Persmentioning
confidence: 99%
“…It shows manageable side effects in interim analysis of a phase I trial in which this agent was evaluated in combination with denosumab in 5 patients. Dysgeusia (62%), fatigue (37%), weight loss (37%), back pain (37%) and headache (37%) were the most frequent AEs [128]. An ongoing trial is evaluating ETC-159 in endometrial cancer alone or in combination with pembrolizumab (NCT02521844).…”
Section: Agents Targeting Cscs In Ec: Clinical Trials and New Persmentioning
confidence: 99%
“…Although remarkable effort has been made in the identification and development of Wnt pathway inhibitors, the on-target toxicity of these drugs, including the disruption of bone and intestine tissues, has limited their clinical utility. However, the use of additional drugs that ameliorate these on-target toxicities has extended the potential of currently available Wnt-inhibiting drugs [130][131][132]. For example, a recent phase I trial result has shown that the co-administration of the PORCN inhibitor ETC-159 along with bone protective treatment in patients harboring solid tumors is safe [132].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of additional drugs that ameliorate these on-target toxicities has extended the potential of currently available Wnt-inhibiting drugs [130][131][132]. For example, a recent phase I trial result has shown that the co-administration of the PORCN inhibitor ETC-159 along with bone protective treatment in patients harboring solid tumors is safe [132]. We have discussed here that CK1α activators show significant efficacy in treating Wnt-driven cancers, without exhibiting on-target toxicity in normal tissue homeostasis at therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of pre-and post-treatment clinical samples, we exploited engineered murine organoids to interrogate the genetics of WNT dependence and WNT-targeted therapy response, but this work has obvious implications for clinical application of WNT therapies. To date, WNT-targeted drugs have performed poorly in early phase clinical studies, owing to on-target dose-limiting toxicity, including bone fractures (51). Recent work has shown that combination of RANKL and PORCN inhibitors provide potent WNT pathway suppression while avoiding adverse bone-related effects (23).…”
Section: Discussionmentioning
confidence: 99%